Accounting and Financial Management : Developments in the international hospitality industry / Edited by Peter Harris & Marco Mongiello - Mongiello, Marco Edited
Presents research and developments in the field of accounting and financial management as it relates to organisations in the international hospitality industry. Draws on researchers' fieldwork and practical experience, and includes case studies and examples from a range of companies across the industry. Covers a number of issues including: performance management, benchmarking, the profit planning framework, room rate pricing decisions, hotel asset management, and lowering risk to enhance firm value